“Sistema de Control Interno para la Ferretería Noble L.G.A. del Cantón La Mana, Provincia de Cotopaxi” - Olvera Anchundia, Auria Germania (2020)
This research project was developed with the purpose of evaluating internal control within the LGA Noble Hardware Store, the difficulty presented by most entities is an inadequate management of the internal control of daily activities and that is one of the problems it presents. The company does not have an adequate order and control in the development of activities, which is exposed to errors in information, fraud, loss, among others. The main reason for the investigation was to identify the problems currently presented by the hardware store, it was possible to identify its shortcomings in the different areas which allowed establishing policies and procedures, so as the main objective of the project was to design an internal control system to improve the process of daily activities in the hardware store. For this research; methods, techniques and instruments were used, an interview with the manager and a survey of the employees, then a SWOT analysis was developed to know the current situation of the company. The internal control evaluations of the activities carried out within the hardware store and identify the risks that exist in each department of the company, as a result in the analysis a high level of risk was obtained. After having done this, the findings were obtained, which is an essential part for the development of the proposal. The contribution was the elaboration of the manual that will allow to establish functions, policies and procedures to improve the development of the activities in each area, the design of manuals will contribute to fulfill the goals and objectives proposed by the company.